The Conservation of Sculpture Parks - Cano, Emilio (Ge-conservacion, 2018)
The Conservation of Sculpture Parks Editor: Sagita Sunara, Andrew Thorn London: Archetype Publications, 2018 ISBN: 9781909492585 Dimensiones: 245 x 170 mm Páginas: 192